Molecular-imaging-based dose painting – a novel paradigm for radiation therapy prescription - Bentzen, Søren M. (2011)
Dose painting is the prescription of a non-uniform radiation dose distribution to the target volume based on functional or molecular images shown to be indicative of the local risk of relapse. Two prototypical strategies for implementing this novel paradigm in radiation oncology are reviewed: sub-volume boosting and dose painting by numbers. Sub-volume boosting involves the selection of a “target within the target”, defined by image segmentation on the basis of the quantitative information in the image or morphologically, and this is related to image based target volume selection and delineation. Dose painting by numbers is a voxel-level prescription of dose based on a mathematical transformation of the image intensity of individual pixels. Quantitative use of images to decide both where and how to delivery radiation therapy in an individual case is also called theragnostic imaging. Dose painting targets are imaging surrogates for cellular or microenvironmental phenotypes associated with poor radioresponsiveness. In this review, the focus is on positron emission tomography (PET) tracers: FDG and choline as surrogates for tumor burden, FLT as a surrogate for proliferation (or cellular growth fraction) and hypoxia sensitive tracers including FMISO, EF3, EF5 and Cu-ATSM as surrogates of cellular hypoxia. Research advances supporting the clinico-biological rationale for dose painting are reviewed as are studies of the technical feasibility of optimizing and delivering realistic dose painted radiation therapy plans. Challenges and research priorities in this exciting research field are defined and a possible design for a randomized clinical trial of dose painting is presented.